(untitled) (The Agriculturists, 2017)
A field experiment was conducted at Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during 2010-2011 to determine the effects and economic performance of urea super granule (USG) and prilled urea (PU) in terms of growth and yield of broccoli and to find out the optimum and economic doses of USG and PU for broccoli in Shallow Red-Brown Terrace Soil under Madhupur Tract. The experiment was laid out in a randomized complete block design with three replications having 17 treatment combinations constituted with different levels of urea super granule (USG) and prilled urea (PU). Result showed that yield of broccoli increased significantly with increasing rate of USG and PU. The treatments containing 160 kg N from USG and 180 kg N from PU exhibited the best performance on yield and yield contributing characters of broccoli having the head yield of 12.9 and 10.6 ton ha-1, respectively. All the yield contributing characters and the economic profitability were favorably correlated with these high yield performing treatments. The performance of USG in terms of growth, yield and yield attributes, head quality (compactness coefficient) and economic profitability was found significantly higher as compared to that of PU. Therefore, USG @ 160 kg N ha-1 and PU @ 180 kg N ha-1 alongwith other recommended fertilizerscould be suggested for broccoli production in terms of yield and economics. From quadratic equation USG @ 163 and 160 kg N ha-1 and PU @ 169 and 160 kg N ha-1 alongwith other recommended fertilizerscould be suggested as optimum and economic doses for broccoli production in Silty Clay Loam Soil of Madhupur Tract. The Agriculturists 2016; 14(2) 95-112